Indirect effects of invasive crayfish on native fish parasites. Issue 4 (26th April 2013) - Pulkkinen, Katja; Ruokonen, Timo J.; Mykrä, Marjut; Tambe, Gordon; Karjalainen, Juha; Hämäläinen, Heikki
Abstract : Interactions between invasive and native species are often modified by parasites. One little‐studied scenario is that invasive species affect parasite transmission to native hosts by altering the relative abundance of hosts needed in parasite life cycles, for example by predation on these hosts. Here we show that presence of an invasive crayfish species, Pacifastacus leniusculus, decreases the mean abundance of native parasites transmitted from snails and aquatic isopods to perch, Perca fluviatilis, in two large boreal lakes in Finland. In contrast, parasites transmitted to the fish from planktonic copepods or mussels, hosts not readily preyed on by crayfish, were not affected by crayfish presence. We suggest that the effect of crayfish on native parasite fauna of fish is mediated via complex effects on invertebrate populations. Hence, our study provides an example of how the indirect ecological effects of species introductions can extend beyond the generally anticipated direct effects, predation and competition.